Effect of injection bleomycin on lymphangioma circumscriptum with keloid formation and secondary infection - Ann Willie Thomas; Emy Abi Thomas; Abhilasha Williams (Wolters Kluwer Medknow Publications, 2022)
Lymphangioma circumscriptum is a microcystic lymphatic malformation localized to an area of the skin, subcutaneous tissue, and muscle which presents with vesiculo-papules or warty lesions, resembling a "frog spawn." Keloids develop due to the proliferation of dermal tissue following skin injury. We present a case of lymphangioma circumscriptum with secondary infection and keloid formation treated with intralesional bleomycin.